Occult Hepatitis B Virus infection in a cohort of patients with chronic Hepatitis C - MI Naga; MA Amin; DA Algendy; AI El Badry; MM Fawzi; AR Foda; SM Esmat; SM Gabal; D Sabry; M Kamal; LA Rashed (Archives of Hepatitis Research - Peertechz Publications, 2019)
Introduction: The prevalence of occult hepatitis B, defi ned by absence of HBsAg and HBV DNA, ranges widely in patients with hepatitis C. This may infl uence the treatment of hepatitis C and the severity of liver disease Aim of work and methods: Was to determine the prevalence of occult hepatitis B virus infection and liver of HBsAg negative patients with chronic hepatitis C and to evaluate its clinical consequences on liver pathology and its impact on the response to treatment with peg-IFNa and Ribavirin. Immunohistochemistry staining for hepatitis B surface antigen and HBV DNA detection was assessed retrospectively on liver biopsies of HCV positive/ HBsAg negative patients before treatment.